2008
DOI: 10.3855/jidc.281
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ureaplasma urealyticum infection with Varicocele-related infertility

Abstract: Background: The role of seminal colonization of Ureaplasma urealyticum in varicocele-related infertility was investigated. Methodology: Semen samples were obtained from infertile patients with or without varicocele and healthy controls and were subjected to routine semen analysis and PCR. DNA was extracted by Cadieux method and analyzed by PCR protocol with species-specific primers for U. urealyticum (urease gene). Results: U. urealyticum was detected by PCR in 23 of 146 (15.75%) semen specimens from infertile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
See 2 more Smart Citations
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…A number of different species of bacteria were assessed to investigate their impact on semen parameters. Thirteen studies investigated the impact of Ureaplasma urealyticum 9,56,63‐65,68,72,75‐78,83,86 and meta‐analyses found that there was a significant deterioration in mean sperm concentration (difference in means: −13.851, 95% CI: −20.938 to −6.763, P = .00, I 2 : 93%; Figure 13), and morphology (difference in means: −2.823, 95% CI: −3.546 to −2.10, P = .00, I 2 : 97%; Figure 14), but no differences in motility (difference in means: 1.471, 95% CI: −5.911 to 8.853, P = .696; Figure 15).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…We found them in infertile men (19.2%) in comparison with the healthy men (11%). In the literature, the prevalence of this infection among infertile men varies – 12%; 15.75%; 24.4% . In most of the cases, the prevalence of ureaplasma is higher in the group of infertile men in comparison with the healthy group studied.…”
Section: Discussionmentioning
confidence: 92%
“…We found them in infertile men (19.2%) in comparison with the healthy men (11%). In the literature, the prevalence of this infection among infertile men varies -12%; 15.75%; 24.4% (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%